(untitled) - Chi, Ch'ao-Ting (London, 1963)
This book introduce the concept of key economic area and its relation to public works for water-control, geographical basis of water-control and economic regionalization in China, a statistical study of the historical development and geographical distribution of water-control activities
Keywords: Flood dams and reservoirs,Irrigation,Public works,Đập và hồ chứa lũ,Thuỷ lợi,Công trình công cộng; China,China,China,Trung Quốc,Trung Quốc,Trung Quốc